Expression of AID in malignant melanoma with BRAFV600E mutation. Issue 5 (May 2014) - Okura, Risa; Yoshioka, Haruna; Yoshioka, Manabu; Hiromasa, Kana; Nishio, Daisuke; Nakamura, Motonobu
Abstract BRAF‐activating somatic mutations often exist in malignant melanoma. The underlying molecular mechanism of somatic BRAF mutation inductions remained to be clear. Activation‐induced cytidine deaminase (AID), a member of a cytidine deaminase family, and APOBEC3B induce somatic mutations and recently have been indicated to be involved in the pathomechanism of several kinds of cancers. The aim of this study was to explore the expression level of AID and APOBEC3B in BRAF‐mutation‐ containing malignant melanoma. Immunohistochemical study demonstrated that 9 of 10 malignant melanomas with high AID expression had BRAFV600E mutation. Eight of them developed multiorgan metastases or multiple lymph node metastases afterwards. Although the size of the patient panel was small, the results indicate that there might be an association between AID expression and BRAF mutation in melanoma.